The Acetazolamide Challenge: Imaging Techniques Designed to Evaluate Cerebral Blood Flow Reserve - Rogg, Jeffrey; Rutigliano, Michael; Yonas, Howard; Johnson, David W.; Pentheny, Susan; Latchaw, Richard E. (American Journal of Neuroradiology, 1989)
Cerebral blood flow was analyzed by the stable xenon (Xe)/CT scanning technique in 29 patients with significant vascular lesions before and after administration of an acetazolamide (Diamox) vasodilatory challenge. Three response types were identified: I, normal flow before Diamox with flow augmentation after Diamox; II, low flow before Diamox with flow augmentation after Diamox; and III, low or normal flow before Diamox with no augmentation or decreased flow after Diamox. Twenty-four percent of the patients studied qualified for category III. We believe that patients in this category represent a group of individuals without blood flow reserve whose clinical management should include careful consideration of their hemodynamic status. The Xe/CT scanning technique with the addition of Diamox flow challenge is a clinically accessible and effective method for assessing cerebral blood flow and blood flow reserve.